2003
DOI: 10.1093/ajcn/78.6.1145
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites increase the dietary lysine requirement in chronically undernourished Indian men

Abstract: On the basis of the 24-h indicator amino acid balance approach, it appears that intestinal infestation with parasites increases the requirement for lysine and that this may be one factor responsible for the higher lysine requirement observed in persons with chronic undernutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…Furthermore, studies in South Asian and rural Indian communities have found parasitic infection in ≤97.4% of the population (30). Such infections increase lysine requirements by ∼50% in adults and in children who are marginally stunted by ∼20% (35,36). The combination of parasitic infestation in addition to consumption of lysine-poor foods exacerbates lysine deficit in an already undernourished population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in South Asian and rural Indian communities have found parasitic infection in ≤97.4% of the population (30). Such infections increase lysine requirements by ∼50% in adults and in children who are marginally stunted by ∼20% (35,36). The combination of parasitic infestation in addition to consumption of lysine-poor foods exacerbates lysine deficit in an already undernourished population.…”
Section: Discussionmentioning
confidence: 99%
“…The difference was small but nevertheless significant. A published observation suggests that intestinal infestation with parasites increased the dietary requirement for lysine, especially in chronically undernourished men in India (24). One of the hall-marks of host immune responses to intestinal parasitic infection in animals, including ruminants, is increased hepatic synthesis and gastrointestinal losses of protein high in sulfur-containing amino acids, such as cysteine and methionine (46).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies in lysine intake decrease protein synthesis and cause weight loss in infants [7]. In addition, protein and amino acid requirements increase during chronic malnutrition and acute infectious disease states, which are commonly present in many developing countries [8, 9]. Under an inflammatory state, non-essential amino acids such as glutamine and arginine become conditionally essential [10].…”
Section: Introductionmentioning
confidence: 99%